IMPROVEMENT OF AVAILABILITY AND MTBF (MEAN TIME BETWEEN FAILURE) OF MINING EQUIPMENT USING SIX M APPROACH (MANPOWER, MATERIAL, MACHINE, METHOD, MEASUREMENT, MOTHER NATURE) - Chrisostomus, Nicholas
Indonesia is a country rich in natural resources like mineral, oil, and gas. Mining is one of the methods for obtaining valuable minerals. This mineral can then be processed further or sold to make profit. Mining will be beneficial for Indonesia’s development as it will generate income for the government. Excellent mine management will ensure that the natural resources are acquired efficiently. Mining activities are dominated by land moving activities, so mainly mechanical and heavy equipment are utilized in the operation. The use of this heavy equipment requires maintenance to maintain its required performance. Productivity of the heavy equipment needs to be maintained to meet the needs of production, as well as to minimize operat ing costs. Two parameters that can be used to evaluate maintenance performance are availability and MTBF. Both parameters can represent parameters that indicate the productivity of the unit. Several approach can be used to solve problems related to availability and MTBF of a unit. This research uses the Six M method to formulate factors that affect availability and MTBF. The problems are grouped and solved based on the root cause. An increase of 9,94% of availability can be achieved by solving manpower related problem in the powertrain component. The framework formulated can also increase the MTBF of the units.